An unusual case of paralytic ileus = Ein ungewöhnlicher Fall eines paralytischen Ileus - Seeßle, Jessica; Stremmel, Wolfgang; Merle, Uta (Zeitschrift für Gastroenterologie, 2012)
A 26-year-old female patient presented with the clinical picture of an acute ileus. Since childhood the patient has been diagnosed as having a MELAS syndrome, a mitochondriopathy. A subtotal colectomy was performed some years ago because of a similar ileus episode. The further diagnostic work-up revealed an expanded small intestine in abdominal radiography. Laboratory analysis showed increased levels of serum lactate with a consecutive respiratory compensated metabolic acidosis. A conservative treatment regime with nasogastric tube, fluid therapy, parental nutrition via peripheral veins and peristalsis inducing drugs was initiated, but did not resolve ileus symptoms. Under the hypothesis that in MELAS syndrome the ileus-related catabolic state aggravates the ileus symptoms in terms of a circulus vitiosus, we started high-caloric parenteral nutrition by using a central venous catheter. A few hours after this intervention, a clear clinical improvement could be observed. Since this initial presentation, the patient was admitted to our hospital several times with the same ileus symptoms. Each of the episodes was successfully and rapidly treated by this high-caloric parenteral nutrition therapy. The reproducible rapid clinical improvement after starting parenteral nutrition supports the hypothesis that an optimal energy supply is the key therapy not only for cerebral but also for gastrointestinal symptoms in patients with MELAS syndrome.